2017
DOI: 10.1002/cssc.201601622
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing Design Principles for Developing Low‐Viscosity Carbon Dioxide‐Binding Organic Liquids for Flue Gas Clean Up

Abstract: Anthropogenic CO emissions from point sources (e.g., coal fired-power plants) account for the majority of the greenhouse gases in the atmosphere. Water-lean solvent systems such as CO -binding organic liquids (CO BOLs) are being developed to reduce the energy requirement for CO capture. Many water-lean solvents such as CO BOLs are currently limited by the high viscosities of concentrated electrolyte solvents, thus many of these solvents have yet to move toward commercialization. Conventional standard trial-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…These include nanomaterial organic hybrids (NOHMs), 29 task-specific protic 30 and conventional ionic liquids, 31 phase-change solvents, 32,33 binding organic liquids (CO 2 BOLs). 34,35 Nearly all of these water-lean solvent systems are projected to be more efficient than aqueous amines but have been limited by nonlinear increases in solvent viscosity during CO 2 uptake. Recently, we showed that, after CO 2 -complexation, singlecomponent CO 2 BOLs do not exist as purely zwitterionic species but rather exist in a dynamic equilibrium between two CO 2 -bound states, an alkyl carbonic acid and a zwitterionic alkylcarbonate.…”
Section: ■ Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…These include nanomaterial organic hybrids (NOHMs), 29 task-specific protic 30 and conventional ionic liquids, 31 phase-change solvents, 32,33 binding organic liquids (CO 2 BOLs). 34,35 Nearly all of these water-lean solvent systems are projected to be more efficient than aqueous amines but have been limited by nonlinear increases in solvent viscosity during CO 2 uptake. Recently, we showed that, after CO 2 -complexation, singlecomponent CO 2 BOLs do not exist as purely zwitterionic species but rather exist in a dynamic equilibrium between two CO 2 -bound states, an alkyl carbonic acid and a zwitterionic alkylcarbonate.…”
Section: ■ Introductionmentioning
confidence: 82%
“…This can be achieved by minimizing the water content, thus enabling regeneration temperatures below 100 °C where low-grade heat could be used to regenerate the solvent. Many solvent classes have been developed based on these principles. These include nanomaterial organic hybrids (NOHMs), task-specific protic and conventional ionic liquids, phase-change solvents, , and our own CO 2 -binding organic liquids (CO 2 BOLs). , Nearly all of these water-lean solvent systems are projected to be more efficient than aqueous amines but have been limited by nonlinear increases in solvent viscosity during CO 2 uptake.…”
Section: Introductionmentioning
confidence: 99%
“…The VLE measurements were performed according the PTx cell principle . A custom test cell developed in‐house was used for simultaneous VLE, kinetics, and physical property measurements of non‐aqueous solvents using less than 50 mL of sample.…”
Section: Methodsmentioning
confidence: 99%
“…CO 2 BOL (IPADM-2BOL). [30][31][32] which is a novel CO 2 binding organic liquid with high cyclic capacity but high viscosity, was chosen to illustrate the impact of viscosity on sensible heat together with ENH-5%H 2 O (Fig. 5).…”
Section: Regeneration Energymentioning
confidence: 99%